NEW AND TRADITIONAL MEDIA AS TOOLS OF INFLUENCE IN THE CONTEXT OF THE ELECTION PROCESS - Дмитро ФОМІН (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article demonstrates the role of traditional and new media, as well as other forms of Internet communications as means of influencing the course of the election process in Ukraine and the formation of public opinion. We focused attention on the fact that in the conditions of transformational processes and political shifts, the level of trust in the latest online means of information dissemination, as well as the intensity of their influence on public opinion, are steadily growing. In this context, the main means and varieties of online communication are characterized, the reasons for their social attractiveness for the politically active part of society are highlighted. The study considered both: positive and negative consequences of the influence of mass media on political processes. The study proved that the positive aspect correlates with the role of communication media, especially online media, as an effective platform for political discussions, active discussion of issues relevant to society, and prompt dissemination of information. The negative aspect is related to the fact that a high level of trust in social networks and messengers can intensify the mechanisms of manipulation and the spread of disinformation. Using the example of the presidential and parliamentary elections in the USA and in Ukraine, we found that the influence of manipulative tools in the media on the course of the election process and the opinion of the electorate has recently been decisive. The study established that further in-depth research on this topic will have significant scientific and practical value, as it will contribute to the effective regulation of mass media activities during elections, as well as make it possible to minimize the risks of media manipulation and engaged coverage of political processes in mass media. Normative and legal regulation of media (in particular, new media and social networks) during elections will create favorable conditions for the development of effective strategies of state-public communication and improvement of interaction between authorities and institutions of civil society.